2022
DOI: 10.3168/jds.2021-20445
|View full text |Cite
|
Sign up to set email alerts
|

Increased adipose tissue lipolysis in dairy cows with fatty liver is associated with enhanced autophagy activity

Abstract: Lipolysis is increased in adipose tissue of cows with fatty liver during the transition period. Autophagy, a major cellular degradation process, plays a critical role in adipose tissue homeostasis. The objective of this study was to explore the relationship between lipolysis and autophagy in adipose tissue of cows with fatty liver. Using a nested case-control design, we compared blood and adipose tissue samples from 10 control cows [parity: median = 3, range = 2-4; days in milk: median = 8 d, range = 5-10 d; h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The results of Chen et al ( 44 ) suggested that the specific species of Firmicutes may induce more hepatic steatosis by modulating fatty acid influx and lipogenesis compared to those of Bacteroidetes . The incidence of fatty liver is particularly high in the high-yielding dairy cows during the postpartum period for the excessive triglycerides deposit in the liver ( 45 ). The shifted relative abundances of Firmicutes and Bacteroidetes may explain the effect of calcium propionate in alleviating NEB.…”
Section: Discussionmentioning
confidence: 99%
“…The results of Chen et al ( 44 ) suggested that the specific species of Firmicutes may induce more hepatic steatosis by modulating fatty acid influx and lipogenesis compared to those of Bacteroidetes . The incidence of fatty liver is particularly high in the high-yielding dairy cows during the postpartum period for the excessive triglycerides deposit in the liver ( 45 ). The shifted relative abundances of Firmicutes and Bacteroidetes may explain the effect of calcium propionate in alleviating NEB.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-GST was purchased from Santa Cruz Biotechnology (#sc-138) and anti-Sin1 from Sigma-Aldrich (#07-2276-I). In bovine liver samples, rabbit monoclonal mTOR Cell Signaling Technology #2983 strongly detected mTORβ and for the detection of full-length mTORα in these samples, a polyclonal antibody against mTOR (ab2732, Abcam) was utilized in line with a previous study ( 35 ). In several of the experiments, proteins of similar sizes (such as Rictor and Raptor or Raptor and mTOR) had to be analyzed on separate gels due to the interference of secondary antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…The liver, through enzymatic oxidation of cholesterol, generates numerous distinct bile acids that play two critical roles: (1) as detergents that facilitate digestion and absorption of dietary lipids, and (2) as steroid hormones that regulate lipid metabolism, energy homeostasis, detoxification, liver regeneration, inflammation, and hepatocarcinogenesis (de Aguiar Vallim et al, 2013). However, elevated levels of fatty acids due to increased lipolysis can damage the liver and potentially impair its functions (Dong et al, 2022;Du et al, 2018), thereby obstructing the biosynthesis bile acids and steroid hormones (i.e., progestogens, androgens, estrogens, etc.). Moreover, elevated fatty acid levels can also compromise oocyte quality, extend the interval from calving to first ovulation, and cause uterine bacterial infections (Ban et al, 2017;Leroy et al, 2008;Van Hoeck et al, 2011;Wathes et al, 2011Wathes et al, , 2012.…”
Section: Production Vs Fertilitymentioning
confidence: 99%